Molecular Diffusion in a Flexible Mesoporous Metal-Organic Framework over the Course of Structural Contraction - Walenszus, Francesco; Bon, Volodymyr; Evans, Jack D.; Kaskel, Stefan; Dvoyashkin, Muslim (Journal of Physical Chemistry Letters, 2020)
In situ 1H pulsed field gradient (PFG) NMR was used to investigate the molecular diffusion of n-butane in the pores of the flexible metal-organic framework DUT-49(Cu) at 298 K at different pore loadings, including pressure ranges below and above the negative gas adsorption (NGA) transition caused by structural contraction of the material. Supported by molecular dynamics simulations, the investigation provided crucial insight into confined diffusion within a highly flexible pore environment. The self-diffusion coefficients were derived from the experiment and compared with simulations, capturing the diffusion during n-butane adsorption and desorption. This complementary approach has yielded experimental characterization of molecular diffusion mechanisms during the unique process of NGA. This includes the observation of a 4-fold decrease of diffusivity within a less than 2 kPa gas pressure variation, corresponding to the NGA transition point.
CRIS-Team Scopus Importer:2022-04-14